1997
DOI: 10.1116/1.580435
|View full text |Cite
|
Sign up to set email alerts
|

Materials processing with intense pulsed ion beams

Abstract: We review research investigating the application of intense pulsed ion beams (IPIBs) for the surface treatment and coating of materials. The short range (0.1–10 μm) and high-energy density (1–50 J/cm2) of these short-pulsed (⩽1 μs) beams (with ion currents I=5–50 kA, and energies E=100–1000 keV) make them ideal in flash heating a target surface, similar to the more familiar pulsed laser processes. IPIB surface treatment induces rapid melt and solidification at up to 1010 K/s causing amorphous layer formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Samples of high purity (99.999%), electropolished single crystal and polycrystalline copper, silicon wafer, 600 grit roughened 75% Cu/25% Ni alloy, and lathe turned aluminum bronze (76% Cu, 14.5% AI, 5.5% Fe, 2% Mn, 2% Co) were placed in the beam path for treatment. Only results for the pure copper and silicon will be reported here; results for the Cu/Ni alloy and aluminum bronze will be re orted in a future publication.…”
Section: Resultsmentioning
confidence: 99%
“…Samples of high purity (99.999%), electropolished single crystal and polycrystalline copper, silicon wafer, 600 grit roughened 75% Cu/25% Ni alloy, and lathe turned aluminum bronze (76% Cu, 14.5% AI, 5.5% Fe, 2% Mn, 2% Co) were placed in the beam path for treatment. Only results for the pure copper and silicon will be reported here; results for the Cu/Ni alloy and aluminum bronze will be re orted in a future publication.…”
Section: Resultsmentioning
confidence: 99%
“…The primary application driving the development of this technology is inertial confinement fusion energy research [2], [3]. Recently, however, these ion beams with ion energies from 50 keV to 10 MeV, ion currents from 1 kA to 10 MA, and pulse durations from 10 to 1000 ns have been finding new applications in diverse fields such as materials processing [4], [5]. Because of the short range of the ions in matter, its application usually involves the surface modification of materials, e.g., implantation [6], alloy mixing [7], [8], defect formation [9], [10], and thin-film deposition [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we define as intense beams with pulse width of 50 to 1000 ns and ion current above 1 kA. Therefore, the pulsed ion beams have been studied for applications in material processings, such as surface treatment of metals, ceramics, and other materials [8][9][10], thin-film deposition [11,12], preparation of ultrafine particles [10,13], ion implantation [14], annealing [15], and other fields of material science. In 1990s, it was found that irradiation of pulsed ion beam on materials achieves adiabatic heating of surface layers at the depth of ion penetration (several hundreds of nanometers) and rapid quenching through thermal diffusion into bulk after irradiation, which is distinguished from the conventional ion beam irradiation technologies.…”
Section: Introductionmentioning
confidence: 99%